Taxonomic review of the genus Compsiluroides Mesnil (Diptera: Tachinidae), with the description of a new species - Huang, Yu-Zen; Tachi, Takuji (Zootaxa, 2019)
Compsiluroides communis Mesnil, C. flavipalpis Mesnil and C. meifengensis sp. nov. are redescribed and described with illustrations. Compsiluroides proboscis Chao & Sun is treated as a junior synonym of C. communis. Variations of structures of the male postabdomen of C. communis are illustrated. The genus is newly recorded from Nepal and Taiwan. A key to the three known species of Compsiluroides is provided and their diagnostic characters are illustrated.